Successful engraftment of gene-corrected hematopoietic stem cells in non-conditioned patients with Fanconi anemia - Rio, Paula; Navarro, Susana; Wei, Wang; Sánchez-Domínguez, Rebeca; Pujol, Roser M.; Segovia, José C.; Bogliolo, Massimo; Merino, Eva; Wu, Ning; Salgado, Rocío; Lamana, María L.; Yañez, Rosa M.; et al. (Nature medicine, 2019)
In an early-phase lentiviral gene therapy trial, gene-corrected autologous hematopoietic stem cells show sustained engraftment and phenotypic correction in non-conditioned patients with Fanconi anemia.